Possible Prophylactic Approach for SARS-CoV-2 Infection by Combination of Melatonin, Vitamin C and Zinc in Animals - Fatima, Sabiha; Zaidi, Syed Shams; Alsharidah, Ashwag Saleh; Aljaser, Feda S.; Banu, Naheed (Frontiers in Veterinary Science, 2020)
SARS-CoV-2, an epidemic causes severe stress both in human and animals and may induce oxidative stress (OS) and increases susceptibility to infection. Domestic animals are found infected by their Covid-2 suffering owners. Chronic immobilization stress (CIS), a model of psychological and physical stress of confinement can trigger depression and anxiety in animals. We evaluated the ameliorative effect of the proposed SARS-CoV-2 prophylactic drugs melatonin, vitamin C and Zinc on CIS induced OS, inflammation and DNA damage in rats. Forty male Swiss albino rats (200-250g, 7-9 weeks old) were divided into five groups as controls, CIS, treated with melatonin (20mg/kg), Vitamin C plus Zinc [VitC+Zn, (250+2.5mg/kg)] alone or in combination (melatonin+vit C+ Zinc) subjected to CIS for 3 weeks. CIS was induced by immobilizing the whole body of the rats in wire mesh cages of their size with free movement of head. Exposure to CIS significantly compromised the circulatory activities of superoxide dismutase, catalase and glutathione with enhanced malondialdehyde, inflammatory markers (IL-6, IL10, TNFα), and lymphocyte DNA damage in comparison to controls. Treatment with melatonin and VitC+Zn alone/or in combination significantly restored the altered biochemical parameters and DNA damage of stressed rats to their respective control values. However, the cumulative action of melatonin with VitC+Zn was more effective in alleviating the CIS induced OS, inflammation and DNA damage. The present study indicates that the antioxidant combination can be an effective preventive measure to combat severe psychological and confinement stress induced biochemical changes in animals due to abnormal conditions such as SARS-CoV-2.